Dynamic Analysis of Competitive Technology Innovation Diffusion Model - Lee, Ming-Chang (Games Review, 2015)
Technological innovation diffusion theory and models play an important position in the forecasting field. Many researchers use these models to predict in different areas. Although the basic Bass model easy to use, but there are many limitations, the effects of Bass diffusion model for innovation diffusion factors (such as price, advertising, income, and technology supply) cannot measure. In order to find the principles of the relationships between innovations and the importance of the affection on the active of an innovation, this paper reviews the application of innovation diffusion models in the field of demand forecasting, through summarizing and analyzing a variety of predication models. Competitive innovation diffusion model include of monopolistic competition in a technology diffusion models and the evolution of the coexistence of two technologies competing diffusion evolution model. Under the aim of this paper, it uses mathematical methods in-depth analysis of competition, technological innovation diffusion models. This mathematical method includes nonlinear equilibrium point, stability analysis. Through the asymmetric evolutionary stability analysis, the paper derived the long-term evolutionary stable equilibrium of the innovation. Finally, the paper gives some suggestions on how to strength the competitive technology innovation in diffusion model.